A compound glass coating with micro-pores to protect SiC-coated C/C composites against oxidation at 1773 K and 1973 K. (February 2022) - Zhu, Xiaofei; Zhang, Yulei; Zhang, Jian; Li, Tao; Xie, Wei; Zhang, Pei; Li, Honggang
Abstract: A compound glass coating with micro-pores, derived from the pre-oxidation of the porous HfSi2 -SiC-Si coating, was fabricated on SiC-coated C/C composites. The coating resisted cracking by introducing micro-pores and compressive stress, which blocked oxygen diffusion and covered penetrable cracks in the SiC inner coating. A dual-layer structure for synergistic anti-oxidation was formed during oxidation at 1773 K and uniformly distributed Hf-oxides reduced the volatilization of SiO2 at 1973 K in the compound glass coating. Therefore, the coating could protect C/C composites against oxidation for 447 h at 1773 K and 45 h at 1973 K. Highlights: The micro-pores and the compressive stress are conducive to inhibiting cracking of the compound glass coating. Hf-oxides particles are evenly distributed in the compound glass coating. A dual-layer structure for synergistic anti-oxidation is formed in the compound glass coating during oxidation at 1773 K. Hf-oxides reduce the volatilization of SiO2 in the compound glass coating during oxidation at 1973 K.